Can Awake Thoracoscopy Procedure be Performed with the Help of Thoracic Paravertebral Anesthesia? (Bangladesh Journal of Medical Science, 2018)
Aim:The aim of this study was to present our experience with 11 patients who were spontaneously breathing with Awake Video Thoracoscopy (AVATS) procedure with the help of TPB because of rareness in the literature.Materials and Methods: Between December 2015 and December 2017, a total of 125 VATS cases were performed; 11 cases underwent VATS operation with the help of TPB; age, gender, operation performed, duration of operation, time of onset of mobilization-oral intake, duration of hospital stay, Visual Analogue Scale (VAS) scores were evaluated retrospectively.Results: All cases were treated with uniportal AVATS procedure with the help of TPB. The mean age was 40,3 ± 17,4 years (range 18-64 years ), nine (82%) of the pateints were male and two (18%) were female. Operation procedures included wedge resection in eight (73 %) patients (six of them for pneumothorax, two of them for diagnosis), in three (27%) patients pleural biopsy (one of them used talc pleurodesis).There were no perioperative events. The mean operation time was 27,7 ± 6,4 minutes (range, 20-40 min) and the mean anesthesia time was 25 ± 3,8 minutes (range 20-30 min).The mean time of mobilizitation, oral intake opening time and length of hospital stay was 1,1 ± 0,4 hours (1-2 hours), 3,5 ± 0,5 hours (3-4 hours), 2,6 ± 0,5 days (2-3 days), respectively.Conclusion:Awake Video Asssited Thoracoscopic Surgery with the help of TPB has less side effects and less complication risks than other awake procedures with the help of other regional anesthesia techniques. We conclude that; although AVATS with the help of TPB has some minor complications, it has advantages such as early discharge, early mobilization and early oral intake, low pain levels in well-selected patient groups.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.576-582